Moral distress in pediatric nurses: A scoping review protocol. - Haiyan Zhou; Huiling Liao; Yuanyuan Huang; Qin Lin; Xin Wang; Huimin Li; Fang Wu; Sha Yang (PLoS ONE)
Introduction Recently, moral distress in pediatric nursing has gained academic attention, yet comprehensive literature reviews on this group are scarce. Aims This study aims to offer a detailed overview of moral distress among pediatric nurses, focusing on understanding its characteristics, prevalence, underlying causes, and consequences on the quality of patient care. Methods Employing a scoping review approach as recommended by the Joanna Briggs Institute, this study will systematically search through PubMed, Scopus, Web of Science, APA PsycInfo, and CINAHL databases using specific search strategies. Titles, abstracts, and full texts will be independently screened by two reviewers according to the eligibility criteria. Relevant data will be extracted, categorized, and subjected to narrative synthesis to draw comprehensive insights. Conclusion The anticipated findings of this study will shed light on the nature, frequency, and drivers of moral distress among pediatric nurses, along with its broader implications for healthcare practitioners, organizational practices, and patient care outcomes.